Desarrollo histórico de satélite terrestre - Hans Peter, Bahr (My University, 1980)
We may state, that linear least-squares interpolation ean generally be applied to LANDSAT imagery, though not always with spectacular success.
Keywords: meteorológico; telecomunicación; navegación; percepción; satélite